Analysis of coupling dynamic characteristics of the high contact ratio spur gear system - HAN Peng; CHEN Songlin; LI Fang; ZHANG Chongyang; SHU Ruizhi; WEI Jing (Jixie chuandong, 2025)
ObjectiveThe high contact ratio (HCR) gear pair basically does not need to increase the weight of the gear device to achieve an increase in carrying capacity and a smoother transmission. Therefore, the use of HCR gears instead of ordinary gears in the transmission system was proposed to improve the load carrying capacity of the gear system and reduce the vibration of the system.MethodsBased on the potential energy method, the time-varying meshing stiffness calculation model of HCR gear was established, and the time-varying meshing stiffness and stiffness fluctuation between HCR gear and ordinary contact ratio gear were compared. The dynamic model of HCR gear system, including shaft segment, spur gear pair and bearing, was established by the finite element method. The dynamic characteristics of the HCR gear system and ordinary contact ratio gear system were compared in different speed conditions.ResultsThe results show that compared with the ordinary contact ratio gear, the comprehensive meshing stiffness of HCR gear is significantly increased, and the stiffness fluctuation is significantly decreased. The root mean square and peak-to-peak values of dynamic meshing force and vibration acceleration of HCR gear system decrease significantly under different speed conditions.